Examining Timeliness of Total Knee Replacement Among Patients with Knee Osteoarthritis in the U.S.: Results from the OAI and MOST Longitudinal Cohorts. (18th March 2020) - Ghomrawi, H.M.K.; Mushlin, A.I.; Kang, R.; Banerjee, S.; Singh, J.A.; Sharma, L.; Flink, C.; Nevitt, M.; Neogi, T.; Riddle, D.L.
Abstract : Background: Patients with knee osteoarthritis may undergo total knee replacement too early or may delay or underuse this procedure. We quantified these categories of total knee replacement utilization in 2 cohorts of participants with knee osteoarthritis and investigated factors associated with each category. Methods: Data were pooled from 2 multicenter cohort studies that collected demographic, patient-reported, radiographic, clinical examination, and total knee replacement utilization information longitudinally on 8, 002 participants who had or were at risk for knee osteoarthritis and were followed for up to 8 years. Validated total knee replacement appropriateness criteria were longitudinally applied to classify participants as either potentially appropriate or likely inappropriate for total knee replacement. Participants were further classified on the basis of total knee replacement utilization into 3 categories: timely (indicating that the patient had total knee replacement within 2 years after the procedure had become potentially appropriate), potentially appropriate but knee not replaced (indicating that the knee had remained unreplaced for >2 years after the procedure had become potentially appropriate), and premature (indicating that the procedure was likely inappropriate but had been performed). Utilization rates were calculated, and factors associated with each category were identified. Results: Among 8, 002 participants, 3, 417 knees fulfilled our inclusion and exclusion criteria and were classified into 1 of 3 utilization categories as follows: 290 knees (8% of the total and 9% of the knees for which replacement was potentially appropriate) were classified as "timely", 2, 833 knees (83% of the total and 91% of those for which replacement was potentially appropriate) were classified as "potentially appropriate but not replaced", and 294 knees (comprising 9% of the total and 26% of the 1, 114 total knee replacements performed) were considered to be "likely inappropriate" yet underwent total knee replacement and were classified as "premature". Of the knees that were potentially appropriate but were not replaced, 1, 204 (42.5%) had severe symptoms. Compared with the patients who underwent timely total knee replacement, the likelihood of being classified as potentially appropriate but not undergoing total knee replacement was greater for black participants and the likelihood of having premature total knee replacement was lower among participants with a body mass index of >25 kg/m 2 and those with depression. Conclusions: In 2 multicenter cohorts of patients with knee osteoarthritis, we observed substantial numbers of patients who had premature total knee replacement as well as of patients for whom total knee replacement was potentially appropriate but had not been performed >2 years after it had become potentially appropriate. Further understanding of these observations is needed, especially among the latter group. Clinical Relevance: Undergoing total knee replacement too early may result in little or no benefit while exposing the patient to the risks of a major operation, whereas waiting too long may cause limitations in physical activity that in turn increase the risk of additional disability and chronic disease; however, little is known about timing of this surgery. We quantified the extent of premature, timely, and delayed use, and found a high prevalence of both premature and delayed use.